(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This article explores the use of gaming technology in the English language instruction process for engineering students. Game technologies in English lessons have long been shown to be an excellent approach to diversify language learning, push students to speak a foreign language, and engage students in an English speaking setting